Pendampingan Pembuatan QRIS, Packaging, Varian Menu Guna Meningkatkan Penjualan UMKM Crispy Oriental Ibu Listy di Kelurahan Baru Ilir, Kota Balikpapan - Ade Alvina; Rizky Nursina; Sri Indah Musliati; Dina Misgi Wulandari; Adi Prihanisetyo (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The Program Activities (PI) held by group 8 started on 29 July 2024 in Baru Ilir Balikpapan Ilir Village and ended on 29 October 2024. A series of activities that have been carried out are assistance in making debit payment methods (QRIS), marketing products through digital applications, attractive packaging and making menu innovations. This Innovation Programme activity aims to increase the competitiveness of Ibu Listy's Crispy Oriental MSMEs with the debit payment method (QRIS), reach a wider market through digital marketing and new menu innovations that are rarely owned. This activity focuses on one of the business actors in Baru Ilir Village.